Research and evaluation of the aromatic hydrocarbons in the polluted wooden railway sleepers - Vilniškis, Rokas; Vaiškūnaitė, Rasa (International Conference “Environmental Engineering”, 2017)
Wooden railway sleepers are impregnated with the chemicals that prevent the disassembling of the wood splitter. Such chemical wood impregnator as creosote or shale oil have been widely used to prolong the lifetime of wooden railway sleepers, protecting them from the negative microorganisms and atmospheric effects. These substances are based on aromatic hydrocarbons (powerful carcinogens), phenolic compounds, heterocyclic nitrogen, oxygen, and sulfur compounds. Lithuania formes over 30,000 pieces of wooden sleepers improper for use annually. Based on the existing environmental legislation, used wooden railway sleepers can not be burned anywehere else except hazardous waste inceneration facilities or can not be buried because of their negative impact on the environment and human health, therefore, this unsuitable wooden sleepers are only stored in their collection or storage areas and they are a major threat to the environment. The aim of this articel is to study how the wooden railway sleepers stored in Vilnius city (Lithuania) are contaminated with the aromatic hydrocarbons using the gas chromatography. Wooden railway sleepers were sam pled and prepared for chemical analysis.